Bioefficacy of botanicalswith special emphasis on Cassia fistula and nano-formulations on survival, growth, and development of insects: A sustainable approach of integrated pest management - Priyanka Saini; Kamal Kumar Gupta
Insects are the most adaptable creatures found all over the world. They affect both the quality and quantity of many crops. The plant contains various secondary metabolites that can hamper insect molting, metamorphosis, growth and development. Cassia fistula is a rich source of amino acids, carbohydrates, fatty acids, flavonoids, proanthocyanidins, and polyphenols, which possess antimicrobial and anti-inflammatory activities. Also, the antifeedant, larvicidal, ovicidal, nymphicidal, and adulticidal properties of these phytocomponents have been documented. Nanoformulations based on plant decoction can act as potent insecticidal agents against insects. Silver nanoparticles (AgNPs) synthesised from C. fistula fruit pulp extract drastically affected the midgut wall of insects and altered their growth and reproduction, ultimately leading to insect death. The potentials of botanicals, C. fistula, and nano-formulations of plant extracts were explored in Insect pest management.